Geological records of South China Sea tsunamis on Penghu Islands, Taiwan. (15th June 2019) - Lu, Cheng-Hao; Yen, Jiun-Yee; Chyi, Shyh-Jeng; Yu, Neng-Ti; Chen, Jia-Hong
Graphical abstract: Highlights: Three layers of tsunami deposits were first identified on Penghu Islands, Taiwan. Embedded in terrestrial deposits, the layers are rich in beach gravels and shells. We devise a systematic method to classify the likelihood of tsunami deposits. Carbon-14 ages of the layers are from AD 300 to 500, 1000 to 1100, and 1400 to 1500. The middle layer may be related to the AD 1076 Guangzhou tsunami of comparable age. Abstract: The coasts around the South China Sea are highly populated and threatened by the ubiquitous tsunamigenic structures of the Manila trench-arc system. However, owing to limited historical records and rare geological findings of tsunamis, our comprehension of and preparation for regional tsunami risks are far from sufficient. Located in the NE South China Sea, the Penghu Islands in Taiwan's western offshore area are selected for a geological tsunami survey because of their advantages of lengthy coastlines and abundant upper Holocene deposits. Three gravel layers of marine incursion events were identified and correlated between three far-separated coastal sections based on the constraints of radiocarbon dating. Intercalated with talus, soil, and dune sand, the gravel layers are poorly sorted, matrix-supported, up to boulder in size, and dominated by marine bioclastics and rounded basalts, which are identical to modern beach gravels. The deposits are located 3–4 m above present sea level, which is significantly higher than the local high tide levels and maximal typhoon surges of 2–3 m high. Furthermore, the deposits are distributed extensively on south-facing shores, indicating relatively large and abnormal inundation events from the South China Sea. Based on the radiocarbon dating results of the event deposits, three tsunamis likely occurred in the periods from the 4th to 6th, 11th to 12th, and 15th to 16th centuries. A recurrence interval of 400–500 years is accordingly associated with these event deposits. These findings demonstrate great tsunami risks exist in the South China Sea basin and call for more attestations and future studies. The major contribution of this study is also supported by the AD 1076 Guangzhou tsunami, which is comparable in age to the middle event deposit.